The International and Political Journal: Rogue States in Western Political Thought - Noam Chomsky - Jacques Derrida as an Example - سعيد, Assist. Prof. Dr : Ruqaya Saeed (The International and Political Journal, 2024)
The concept of „rogue states‟ has witnessed several modifications depending on the change in American foreign policy and those who succeeded in drawing it up and influencing it. Many synonyms and terms have been formed to give a complete meaning to „rogue states‟. United States President, Ronald Reagan, used the term “evil empire” to describe the Soviet Union during the Cold War era, and he used this concept to express the American view of its main enemy, as a „rogue state‟. Henri Kissinger reinforced this concept to describe the Soviet Union as an outlaw empire which did not hesitate to commit any crime in order to achieve its goals. The expression of this concept by U. S. presidents, successively, confirms the true significance of the concept‟s meaning in the mind of the American leaders. It is entrenched according to intellectual propositions in terms of its origin, political and war behavior, in addition to the mechanism of influence of the „rogue states‟ on American national security, especially after the repercussions of the events of September 11, which is considered as a main event to attack vital institutions inside the United States, including the Pentagon building. The concept of „rogue states‟ includes states that carry out military actions. Or, in the American point of view, terrorist states or axis of evil since they harm the security of other states or constitute a provocative compass to destabilize their national security. The concept of rogue states was modified during the era of Presidents Barack Obama and Donald Trump. Thus, it came to refer to states that use missile force for maneuver or perform military parades to send an implicit message. This study sheds light on the most important intellectual proposals that constitute a model for contemporary Western political thought, represented by Noam Chomsky and Jack Derrida.